2011
DOI: 10.1007/s00726-011-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

Taurine protects rat testes against doxorubicin-induced oxidative stress as well as p53, Fas and caspase 12-mediated apoptosis

Abstract: The protective effect of taurine against doxorubicin-induced testicular oxidative stress and apoptosis was investigated in rats. Male rats 8 weeks of age were treated with doxorubicin alone (3 mg/kg, i.p. every other day for 3 doses), taurine alone (150 mg/kg, i.p. every other day for 3 doses) or taurine plus doxorubicin (each dose given 1 day post-taurine). After 28 days, rat testes were collected and analysed. Rats treated with doxorubicin alone displayed reduced body and testicular weights, decreased sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 64 publications
(60 reference statements)
9
61
1
Order By: Relevance
“…The results showed that GPx was elevated and MDA was reduced when DXR was given in conjunction with taurine in comparison to administration of DXR only. The authors concluded that oxidative stress played a role in DXR-induced testicular toxicity and that taurine alleviated this toxicity [19]. When we compared the groups in our study with regard to MDA and GPx, we observed a similar relationship, in which the level of MDA was lower but that of GPx was higher in the DXR + RA group than the DXR group.…”
Section: Discussionsupporting
confidence: 68%
“…The results showed that GPx was elevated and MDA was reduced when DXR was given in conjunction with taurine in comparison to administration of DXR only. The authors concluded that oxidative stress played a role in DXR-induced testicular toxicity and that taurine alleviated this toxicity [19]. When we compared the groups in our study with regard to MDA and GPx, we observed a similar relationship, in which the level of MDA was lower but that of GPx was higher in the DXR + RA group than the DXR group.…”
Section: Discussionsupporting
confidence: 68%
“…Adding TA does not make it toxic in cells where it is already present in high concentration. Moreover, supplementation with TA (150 mg kg -1 or ~1.87 g L -1 ) in a recent study (20) prevented oxidative stress induced by doxorubicin. However, concentrations this high may lead to saturation.…”
Section: Discussionmentioning
confidence: 95%
“…These include various vitamins, propolis, sulphhydryl compounds, and plant products (15)(16)(17)(18)(19). Taurine (TA) (2-aminoethanesulfonic acid) is found in high concentrations in various mammalian tissues (20). Sung et al (21) reported that TA suppressed oxidant-induced tissue injuries by stabilising the biomembrane and by scavenging free radicals (21).…”
mentioning
confidence: 99%
“…Group II rats were exposed to NaF in drinking water at 15 mg/L alone [21]. Group III rats were orally administered taurine at a dose of 200 mg/kg using drinking water as vehicle [22]. Groups IV rats were co-administered with NaF and taurine at 100 mg/kg (TAU 1).…”
Section: Experimental Protocolmentioning
confidence: 99%